The 7 Habits of Highly Effective Teenagers : The Ultimate Teenage Success Guide - Covey, Sean (London Simon & Schuster, 2014)
Now, the bestselling 7 Habits are available to a new generation - teenagers and those who love them.
Include Illustrations, Bibliography and Index
Keywords: Teenagers--Conduct of life -- Self-help techniques for teenagers -- Self-realization -- Success--Psychological aspects